1993
DOI: 10.1007/bf01046051
|View full text |Cite
|
Sign up to set email alerts
|

Integrated play groups: A model for promoting the social and cognitive dimensions of play in children with autism

Abstract: This investigation provides a description of a multifaceted model to promote peer play, and an evaluation of its impact on the social and cognitive dimensions of play in three children with autism. A combination of quantitative and qualitative methodologies were used to evaluate the effectiveness of the model application. A multiple-probe design across participants demonstrated (a) decreases in isolate play and collateral gains in more social forms of play, and (b) decreases in stereotyped object play and coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
96
0
13

Year Published

2001
2001
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(113 citation statements)
references
References 26 publications
4
96
0
13
Order By: Relevance
“…One such approach, the Integrated Play Group (IPG) model, can be described as "adult-facilitated peer mediation" due to its use of typically developing peers and adult guidance. The IPG model attempts to physically arrange the environment in order to foster mutually enjoyable social interaction, communication, play, and imagination experiences between children with autism and typical peers or siblings (Wolfberg & Schuler, 1993, 1999. It proposes that children with autism maximize their developmental potential by participating in play activities with more capable peers.…”
Section: Integrated Play Group (Ipg)mentioning
confidence: 99%
“…One such approach, the Integrated Play Group (IPG) model, can be described as "adult-facilitated peer mediation" due to its use of typically developing peers and adult guidance. The IPG model attempts to physically arrange the environment in order to foster mutually enjoyable social interaction, communication, play, and imagination experiences between children with autism and typical peers or siblings (Wolfberg & Schuler, 1993, 1999. It proposes that children with autism maximize their developmental potential by participating in play activities with more capable peers.…”
Section: Integrated Play Group (Ipg)mentioning
confidence: 99%
“…Among the strategies/accommodations that an educational assistant can provide for a student with ASD in the classroom are: -Increasing physical proximity to peers -Fading assistance to allow for more natural peer interaction opportunitiesPartnering student with ASD with peers during academic tasks -Verbally highlighting similarities between student with ASD and peers -Creating communication cards focused on social exchanges -Teaching peers how to communicate with target student using sign language gestures -Utilizing interactive technology -Giving student with ASD classroom responsibilities that encourage interaction with peers (Causton-Theoharis, J., & Malmgren, 2005, p. 436) Social skills training programs are another possible response to the need for individualized training in reciprocal play and conversational skills for children with ASD. While social skills training programs have been shown to have a positive effect on problem-solving skills in children with ASD (Embregts & van Nieuwenhuijzen, 2009;McConnell, 2002;Wolfberg & Schuler, 1993), these programs can lack social validity in terms of generalization of skills outside of the training sessions (Haring & Breen 1992;Ozonoff & Miller, 1995). Haring and Breen (1992) found that social skills training packages, while useful in terms of determining existing levels of social competence, may not translate into friendship relationships outside of the training context.…”
Section: Fostering Genuine Relationshipsmentioning
confidence: 99%
“…Data from children with autism are also suggestive of a such a substrate: children with autism generally do not pretend play nor learn language normally (half never speak, and the other half do so late). Further, children with autism who do engage in some pretending are generally those whose language skills are more advanced (Jarrold, Boucher, & Smith, 1993;Wolfberg & Schuler, 1993). Future research should be aimed at exploring these relations.…”
mentioning
confidence: 99%